Singing under the impulsiveness: impulsivity in psychiatric disorders. Issue 2 (3rd April 2018) - Kulacaoglu, Filiz; Kose, Samet
ABSTRACT: Impulsivity is a key feature of numerous psychiatric disorders. This paper reviews the recent evidences on the impulsivity in elderly, relationship between impulsivity and borderline personality disorder (BPD) with attention-deficit/hyperactivity disorder (ADHD), impulsivity with anxiety and mood disorders, and the psychopharmacological approaches to impulsivity evaluating previously published studies. A literature review of the theoretical bases of the relationship between psychiatric disorders and impulsivity is presented. Measurements of impulsivity and neurobiological hypothesis are defined. Treatment approaches are discussed. Previous researches have shown significantly higher levels of impulsivity among patients with BPD, ADHD, anxiety, and mood disorders. In addition, older adults could be more impulsive than younger adults. But the nature of this relationship remains unclear. This is probably due to the fact that there is much overlap between them. Impulsivity is a risk for suicidality and influences pathogenesis, course, clinical severity of many psychiatric disorders. Pharmacological interventions for treating impulsivity should be incorporated into treatment plans for these disorders. Identifying the role of pharmacological interventions in modulating the development of trait impulsivity may prevent progression to psychiatric disorders and associated adverse consequences.